ANALISIS KETERKAITAN HAK ASASI MANUSIA DALAM PRAKTIK EUTHANASIA PASIF: STUDI KASUS DI NEGARA YANG MELARANG (INDONESIA) DAN MELEGALKAN (BELGIA) - Widyaningsih, Elis Dwi; Lesmana, Sri Jaya; Indayatun, Ratna (SOSCIED, 2025)
Human rights are basic rights that are inherent in every individual from birth, regardless of race, religion, nationality, or social status. In this context, the right to life is one of the most fundamental and universally recognized rights. However, the development of medical technology and contemporary social dynamics have given rise to new debates about the interpretation of the right to life, especially when faced with the practice of passive euthanasia, i.e. the termination of medical procedures on terminally ill patients. This study aims to analyze the comparison of euthanasia practices in relation to human rights in Indonesia and Belgium. Indonesia is guided by the principle of the sanctity of life which is contrary to the practice of passive euthanasia. Meanwhile, in Belgium, euthanasia regulations are more systematic. This study uses normative legal research methods with a comparative approach. The results of the study show that the legal policies of euthanasia in Indonesia and Belgium have striking differences, especially in terms of regulation and legal protection. Belgium already has a comprehensive legal system and clear oversight mechanisms, which provide certainty and protection for medical personnel and patients alike. Meanwhile, in Indonesia, there is no explicit regulation regarding passive euthanasia, thus causing legal, ethical, and social dilemmas in its implementation. The researcher recommends the importance of cross-sectoral discourse in Indonesia to formulate policies or ethical guidelines that consider human rights values, religious norms, and local socio-cultural contexts in a balanced and responsible manner.